Formation of carbonate or benzoate esters via nitrosocarbonyl compounds - Mindl, Jaromír (Univerzita Pardubice, 1996)
A novel on-vessel oxidation and subsequent solvolysis of hydroxamic acids in the presence of lead(IV) oxide have been explored.